Korelasi Ukuran, Berat, Dan Indeks Telur Dengan Performa Penetasan Iguana Hijau (Iguana iguana) - Ahmad Ilmul Muhashona (2020)
The aim of the study is found correlation of egg index, egg mass and egg sizes such as height, width with hatchling performance. The correlation was examined for 27 green iguana eggs from the Faculty of Veterinary Medicine, Airlangga University. Egg mass and egg sizes, e.g height, width, and index were taken twice on a day old of oviposition and 90 day old of oviposition, hatchling performance, e.g SVL, STL, and hatchling mass is taken when day old hatchling. The data has been collated and analyzed using regression analysis in IBM SPSS 23. The results showed significant coefficients of egg’s height and width of a day old and 90 day old of oviposition amongs SVL 0.000 (p<0.05), and 0,063 (p>0.05). Egg’s height and width of a day and 90 day old of oviposition was positively correlated with STL, with an significant coefficient of 0.000 (p<0.05) and 0.008 (p<0.05). Moreover, an increase in egg mass was also accompanied by an increase in hatchling mass. The mass of eggs scaled with hatchling mass to the significant coefficient of 0.000 (p<0.05). The egg’s height and width of 90 day old of oviposition amongst SVL and index of eggs both a day old and 90 day old of oviposition amongst hatchling mass has no positive correlated.